Microcrystal Delivery Using a Syringe and Syringe Pump Method for Serial Crystallography - Ki Hyun Nam (Analytica)
Serial crystallography (SX) determines the crystal structures of target molecules at room temperature with minimal radiation damage. During SX data collection, the stable delivery of many microcrystals to the X-ray interaction point is crucial for efficient sample consumption and effective beamtime usage. Most microcrystal delivery techniques for SX require sophisticated devices or specialized techniques, which can be challenging for data collection. This review introduces a straightforward method that delivers microcrystal samples in SX experiments using a commercially available syringe and syringe pump. This method does not require specialized skills for sample delivery and can be tested in the laboratory prior to SX data collection at the beamline. Advantages and disadvantages of this method are also discussed, along with various application cases. This straightforward sample delivery approach is concluded to facilitate efficient SX data collection.